Specialist registrar training: ideas for a five year programme. Issue 5 (September 1997) - Williams, L; Pritty, P; Esberger, D
Abstract : Proposals for specialist registrar training in accident and emergency medicine in Mid-Trent Region are outlined. These may provide a framework for other schemes as well as stimulating further ideas.